Pengaruh Budaya Organisasi Terhadap Produktivitas Pegawai Pada UPT SMAN 3 Wajo Di Kabupaten Wajo - Murdaya Murdaya; Eva Agustiany P; Nurul Aqsa (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2023)
Every organization is established based on certain goals and targets. Likewise with school. Every school has its own goals. This goal will not be realized without the support of adequate human resources. Because human resources are very influential on the success or failure of a school in achieving goals. Every school always tries to increase employee productivity in order to survive, develop and have high trust from outsiders. In order to increase employee productivity, it is often necessary to improve and improve the human resources of employees. However, activities to increase the human resources of employees often do not achieve what they expect, namely achieving the goals of the school organization such as increasing employee productivity. Even though they already have the resources qualified employees, employees may not necessarily be able to provide good work results for school organizations if they are still in the shackles of a work culture that is less supportive and not conducive. This research is a type of quantitative research using a survey approach which intends to test the combination/influence of the independent variables on the dependent variable, namely organizational culture on employee productivity at UPT SMAN 3 Wajo. The number of samples taken from UPT SMAN 3 Wajo employees is 40 people from the total employees. there are 67 people. Based on the results of data processing using the SPSS 22 for windows program where a person correlation value of 528 was obtained, this shows that between organizational culture and employee productivity at UPT SMAN 3 Wajo is in a fairly strong category and a relation coefficient (R) is obtained of 0.528 which shows that the relationship between Organizational Culture variables and employee productivity at UPT SMAN 3 Wajo is in a fairly strong category.